ASEAN DAN KETAHANAN PANGAN - Dinna Wisnu (Sekretariat Jenderal DPR RI, 2013)
Food Security is strategic for ASEAN countries, but the achievement is far from expectation from year to year. Poverty, access to food and nutrition is concerning. This paper focuses on the perspective of policymaking and inter-governmental cooperation on food security, which is argued as obsolete. A policy-making model where governments direct their attention to producers through subsidies, import, import quota, and joint-effort to collect grains for difficult times is actually prolonging mismatch of policy approach for producers and consumers, obstructing agribusiness development, increasing the risk for food price inflation also enforcing farmers and fishermen to leave their jobs. A model of food policy is recommended where food policy would be based on employment protection, provision of instrument for cooperation between communities and capacity development program for agribusiness. Farmers, fishermen and agribusiness are subjects and need to be equipped with innovation and infrastructure to compete well in this sector.